Isolation and identification of two major viruses infecting bell pepper in Karnataka - and S.J. SINGH, T.E. GEORGE, N. ANAND (Indian Phytopathology, 2002)
On the basis of symptomatology, reaction on indicator plants, particle morphology serology, the two major viruses infecting bell pepper (Capsicum annuum L.) in and around Bangalore were identified as potato virus Y (PVY) and cucumber mosaic virus (CMV).